Technology of efficient continuous erythritol production from glycerol. (15th December 2016) - Rakicka, Magdalena; Rukowicz, Beata; Rywińska, Anita; Lazar, Zbigniew; Rymowicz, Waldemar
Abstract: Erythritol production in chemostat culture from pure and crude glycerol with different nitrogen sources by Yarrowia lipolytica Wratislavia K1 was investigated. Moreover, a process of erythritol purification based on ion exchange is proposed. The highest erythritol production (103.4 g L −1 with a volumetric erythritol production rate of 1.12 g L −1 h −1 and a yield of 0.52 g g −1 ) was obtained by applying an inorganic nitrogen source (4.6 g L −1 of ammonium sulfate). Very promising results were also obtained when pure glycerol was replaced with crude glycerol as a carbon source. During this culture yeast produced 81.9 g L −1 of erythritol, which corresponded to a 0.9 g L −1 h −1 volumetric erythritol production rate and a yield of erythritol production of 0.4 g g −1 . The fermentation broth was desalinated and decolorized by ion exclusion, ion exchange and sorption on activated carbon. The final solution contained only erythritol. The presented technology follows the vision of a circular economy by turning waste into products and using renewable materials as a feedstock. This study supports the potential of the industrially relevant wild type Yarrowia lipolytica strain for intensified and efficient erythritol production. The proposed technology is ecofriendly, requires a small number of purification steps and generates low amount of wastes. The final solution is rich in erythritol and can be applied directly as a sweet low-calorie food additive. Highlights: The study propose a technology of efficient continuous erythritol production from glycerol. Pure and crude glycerol promoted economical erythritol biosynthesis in chemostat culture. Continuous biosynthesis of erythritol with low amounts of undesirable byproducts. The post-fermentation solution was desalinated and decolorized by combining ion exclusion, ion exchange and activated carbon.